Penerapan Design Thinking Pada Perancangan Website Cafe Hasbeans - Firdi Firsnandio Saddam; Dedy Setiawan; Muhammad Razi A. (STMIK Banjarbaru, 2026)
Hasbeans is a café located in Jambi that offers coffee, non-coffee beverages, food, and reservation services. The current ordering process, which uses barcode scanning redirected to Google Drive, is considered inefficient because it can cause queues and slow down service. In addition, the café requires an information platform to support marketing and branding activities. This study aims to design a UI/UX-based website information system for Café Hasbeans using the Design Thinking method, which consists of empathize, define, ideate, prototype, and test stages. The result of this study is a website prototype designed to help customers access menu information, events, and café information more effectively and efficiently. Prototype testing was conducted using Maze with 10 customer respondents, 3 admin respondents, and 1 super admin respondent. The results showed Maze Usability Scores of 89 for customers, 99 for admins, and 97 for the super admin, indicating that the UI/UX design is easy to understand, easy to learn, and well accepted by users.Keywords: Design Thinking; Maze; UI/UX; Usability Testing AbstractHasbeans merupakan café di Kota Jambi yang menyediakan menu coffee, non-coffee, makanan, serta layanan reservasi tempat. Proses pemesanan yang masih menggunakan scan barcode dan dialihkan ke Google Drive dinilai kurang efisien karena dapat menimbulkan antrian dan memperlambat pelayanan. Selain itu, café juga membutuhkan media informasi untuk mendukung pemasaran dan branding. Penelitian ini bertujuan merancang UI/UX sistem informasi Café Hasbeans berbasis website menggunakan metode Design Thinking yang meliputi tahap empathize, define, ideate, prototype, dan test. Hasil penelitian berupa prototype website yang memudahkan pelanggan mengakses informasi menu, events, dan informasi café secara efektif. Pengujian menggunakan Maze dilakukan kepada 10 pelanggan, 3 admin, dan 1 super admin dengan hasil Maze Usability Score sebesar 89 untuk pelanggan, 99 untuk admin, dan 97 untuk super admin, sehingga rancangan dinilai mudah dipahami dan diterima pengguna.